Diacylglycerol kinase zeta regulates Rac1-mediated remodeling of the actin cytoskeleton - Abramovici, Hanan (University of Ottawa (Canada), 2008)
The lipid second messengers diacylglycerol (DAG) and phosphatidic acid (PA) regulate the activity and localization of actin reorganizing proteins that participate in cellular shape changes underlying important biological processes. DAG kinases (DGKs) phosphorylate DAG to yield PA, thereby attenuating the activity of DAG-activated proteins and stimulating proteins that respond to PA. Using cell biological and biochemical approaches, I explored the hypothesis that DGKzeta regulates actin cytoskeleton remodeling in mammalian cells by associating with and promoting the activity of the Rho GTPase Rac1 and the Rac1-activated kinase PAK1. I found that DGKzeta forms a complex with both proteins, and that PA from DGKzeta promotes the release of Rac1 from its inhibitor RhoGDI, triggering Rac1 activation. DGKzeta also regulates the localization and activity of PAK1. Furthermore, the ability of DGKzeta to promote Rac1 activity appears to underlie important physiological processes requiring the restructuring of the actin cytoskeleton such as cell migration, neurite outgrowth, and myoblast fusion. Localization of signaling complexes to specific cellular domains is required for complex changes in cell morphology. Because subcellular localization is critical for DGKzeta function, I investigated the molecular mechanisms underlying its targeting to different cellular compartments. I found that both PKC-mediated phosphorylation of the MARCKS domain and binding of the C-terminus to syntrophins regulate DGKzeta recruitment to the plasma membrane. Collectively, my results define a molecular mechanism that regulates the recruitment of DGKzeta to the membrane and that couples changes in DAG and PA to the activation of PAK1 and Rac1. These findings have uncovered a novel role for DGKzeta in actin cytoskeleton organization.
Keywords: Biology, Neuroscience.